2009
DOI: 10.12702/1984-7033.v09n03a10
|View full text |Cite
|
Sign up to set email alerts
|

Embryogenic calli induced in interspecific (Elaeis guineensis x E. oleifera) hybrid zygotic embryos

Abstract: -The hybridization between oil palm (Elaeis guineensis)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Also, adventitious shoot apical meristem surrounded by leaf primordia was observed and distinguished by presence of vascular connection with the maternal tissue ( Figure 6H1) as shoot organogenesis. The results of the current study are on line with those of Angelo et al (2009), Demeter et al ( 2010), Elviana et al ( 2011) and Steinmacher et al (2011) who reported that protodermis was a unique character and the first tissue identified somatic embryogenesis development .…”
Section: Histological Analysissupporting
confidence: 91%
“…Also, adventitious shoot apical meristem surrounded by leaf primordia was observed and distinguished by presence of vascular connection with the maternal tissue ( Figure 6H1) as shoot organogenesis. The results of the current study are on line with those of Angelo et al (2009), Demeter et al ( 2010), Elviana et al ( 2011) and Steinmacher et al (2011) who reported that protodermis was a unique character and the first tissue identified somatic embryogenesis development .…”
Section: Histological Analysissupporting
confidence: 91%
“…The induction of shoots on poly-embryogenic complexes was proven successful [12,13] as proposed earlier for the interspecific hybrids [45]. Cultivating poly-embryogenic complexes in medium supplemented with abscisic acid [9] before shoot induction might contribute to synchronization [46].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, in a genetic improvement program, cloning from ZE can accelerate culture selection cycles. This is especially true in backcross generations, where each embryo represents a unique genotype, for permitting the replication of experiments in different locations or conditions, reinforcing the representation of the environment throughout the multiple steps of the selection process (Angelo et al 2009;Balzon et al 2013).…”
Section: Introductionmentioning
confidence: 99%